How architects write - Spector, Tom; Damron, Rebecca (New York Routledge, 2013)
This is the first writing reference book for architects, landscape architects, interior designers or industrial designers including examples of designers$1 (Bmanifestos, statements of design intent, proposals, research reports, specifications and much more.s
Keywords: DESIGN JOURNALS; HISTORY TERM PAPERS; RESEARCH REPORTS; BUSINESS DOCUMENTS; DESIGN PHILOSOPHY; MANIFESTOS; ARCHITECTURE EDUCATION (AR-EDU)